2001
DOI: 10.1074/jbc.m107656200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Tumor-promoter Okadaic Acid Bound to Protein Phosphatase-1

Abstract: Protein phosphatase-1 (PP1) plays a key role in dephosphorylation in numerous biological processes such as glycogen metabolism, cell cycle regulation, smooth muscle contraction, and protein synthesis. Microorganisms produce a variety of inhibitors of PP1, which include the microcystin class of inhibitors and okadaic acid, the latter being the major cause of diarrhetic shellfish poisoning and a powerful tumor promoter. We have determined the crystal structure of the molecular complex of okadaic acid bound to PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
144
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(155 citation statements)
references
References 36 publications
8
144
1
2
Order By: Relevance
“…Egloff et al (1995) investigated the nature and function of the two metal ions (Mn 2+ and Fe 2+ or Fe 3+ ) and reported that metal ions promote hydrolysis reactions by activating water molecules and stabilizing nucleophilic hydroxide and oxide ions. Figure 14 shows the molecular surface of the catalytic subunit of PP1-microcystin-LR complex (Goldberg et al 1995), and similar crystal structures of the molecular complex of catalytic subunit of PP1-okadaic acid (Maynes et al 2001), PP1-calyculin A (Kita et al 2002), and PP1-motuporin (Maynes et al 2006) have also been reported.…”
Section: Nodularinmentioning
confidence: 97%
See 3 more Smart Citations
“…Egloff et al (1995) investigated the nature and function of the two metal ions (Mn 2+ and Fe 2+ or Fe 3+ ) and reported that metal ions promote hydrolysis reactions by activating water molecules and stabilizing nucleophilic hydroxide and oxide ions. Figure 14 shows the molecular surface of the catalytic subunit of PP1-microcystin-LR complex (Goldberg et al 1995), and similar crystal structures of the molecular complex of catalytic subunit of PP1-okadaic acid (Maynes et al 2001), PP1-calyculin A (Kita et al 2002), and PP1-motuporin (Maynes et al 2006) have also been reported.…”
Section: Nodularinmentioning
confidence: 97%
“…As Uemura and Hirata (1989) suggested (Fig. 13), a hydrogen bond formed by a cyclic structure between the C-1 acid and the C-24 (Uemura and Hirata 1989) hydroxyl group was confirmed in both free okadaic acid and the PP1-okadaic acid complex (Maynes et al 2001). The acid motif in okadaic acid accepts a hydrogen bond from the hydroxyl group of Tyr 272 in PP1, and the esterification or removal of the acidic moiety in okadaic acid results in elimination of its inhibitory activity.…”
Section: Okadaic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…1A). 9,15,16 The general lack of inhibition exhibited by the PPP-family members PP2B and PP7 in the presence of these compounds, coupled with differential inhibition of the remaining PPP-family enzymes by select toxins, has made these small molecules invaluable tools in protein phosphatase research by helping implicate distinct protein phosphatases in various cellular processes. Recently, we reported two additional PPPfamily protein phosphatases from A. thaliana (AtSLP1 and -2 phosphatases) that demonstrated complete insensitivity to inhibition by both microcystin and okadaic acid, with AtSLP1 exhibiting slight enzymatic activation.…”
Section: Introductionmentioning
confidence: 99%